Pharmacological basis for the medicinal use of Morus alba in gut and airways disorders - Munasib Khan; Najeeb-; Arif-ullah Khan; Anwar Hassan Gilani (Bangladesh Pharmacological Society, 2012)
Crude extract of Morus alba at 100 mg/kg exhibited protective effect against castor oil-induced diarrhea in mice. In isolated rabbit jejunum, M. alba (0.3-10 mg/mL) inhibited the spontaneous contractions and caused glibenclamide-sensitive inhibition of low K+ (20 mM)-induced contractions, with mild effect on high K+ (80 mM). Similarly, cromakalim caused inhibition of low K+, but not of high K+, while verapamil did not differentiate in its inhibitory effect on two concentrations of K+. M. alba (3.0-30 mg/kg) caused suppression of carbachol (100 µg/kg)-induced increase in inspiratory pressure of anaesthetized rats. In guinea-pig trachea, M. alba completely inhibited low K+ contractions, with partial effect on high K+. M. alba (0.3-1.0 mg/mL) caused leftward shift of isoprenaline-induced inhibitory concentration response curves, like papaverine. These results indicate that M. alba possesses a combination of KATP channel opening, weak Ca++-antagonist and phosphodiesterase inhibitory mechanisms, which explain its medicinal use in hyperactive gut and airways disorders.